الضغوط النفسية وعلاقتها بممارسة العنف المدرسي لدى تلاميذ المرحلة الثانوية - دراسة ميدانية ببعض ثانويات ولاية الأغواط – (مجلة الواحات للبحوث والدراسات, 2022)
ملخص: هدفت الدراسة الحالية إلى معرفة العلاقة بين الضغوط النفسية و ممارسة العنف المدرسي عند عينة من تلاميذ بعض  ثانويات ولاية الأغواط تبلغ 700 تلميذا موزعة على الجنسين(ذكور، إناث) مسجلين في العام الدراسي الحالي 2020/2021، وخلصت الدراسة إلى النتائج التالية: - وجود علاقة ارتباطية قوية بين الضغوط النفسية و ممارسة العنف المدرسي. - وجود فروق في الضغوط النفسية والعنف المدرسي تبعا لمتغير الجنس والمنطقة. الكلمات المفتاحية: ضغوط نفسية , عنف مدرسي , مناطق حضرية , مناطق شبه حضرية. Abstract- The aim of this study is to find out the relationship between psychological stresses and the school violence behavior. The study is carried out on students from some secondary schools in the Wilaya of Laghouat. This investigation has covered 700 students, both genders included, enrolled in 2020-2021. The conclusions drawn from this study are highlighted as follows:-          The school violence behavior depends strongly on the psychological stresses-          Psychological stresses and the school violence behavior depend on the gender and the area of the student.Keywords: Psychological stresses; school violence behavior; urban area; semi-urban area